Uncovering the components of the Francisella tularensis virulence stealth strategy - Jones, Bradley D.; Faron, Matt; Rasmussen, Jed; Fletcher, Josh (Frontiers in Cellular and Infection Microbiology, 2014)
Over the last decade, studies on the virulence of the highly pathogenic intracellular bacterial pathogen Francisella tularensis have increased dramatically. The organism produces an inert LPS, a capsule, escapes the phagosome to grow in the cytosol (encoded by the FPI genes) of a variety of host cell types that include epithelial, endothelial, dendritic, macrophage and neutrophil. This review focuses on the work that has identified and characterized individual virulence factors of this organism and we hope to highlight how these factors collectively function to produce the pathogenic strategy of this pathogen. In addition, several recent studies have been published characterizing F. tularensis mutants that induce host immune responses not observed in wild type F. tularensis strains that can induce protection against challenge with virulent F. tularensis. As more detailed studies with attenuated strains are performed, it will be possible to see how host models develop acquired immunity to Francisella. Collectively, detailed insights into the mechanisms of virulence of this pathogen are emerging that will allow the design of anti-infective strategies.